Trends in Exposure to Secondhand Smoke Among Adolescents in China From 2013-2014 to 2019: Two Repeated National Cross-sectional Surveys - Chuanwei Ma; Yayang Huang; Sixuan Li; Min Zhao; Xinying Zeng; Xinbo Di; Costan G Magnussen; Bo Xi; Shiwei Liu (JMIR Publications, 2023)
BackgroundIt is well-known that secondhand smoke exposure in childhood or adolescence is positively associated with morbidity and mortality. However, less is known about the current status of and most recent trends in secondhand smoke exposure among adolescents in China. ObjectiveWe aimed to assess recent changes in the prevalence of secondhand smoke exposure among adolescents in China using nationally representative data. MethodsWe used data from 2 repeated national cross-sectional surveys conducted in 2013-2014 and 2019. A total of 155,117 students (median age 13.5 years) in 2013-2014 and 147,270 students (median age 13.1 years) in 2019 were included in this study. Sociodemographic factors and secondhand smoke exposure information were collected via a standardized questionnaire. Exposure was defined as secondhand smoke exposure ≥1 day during the past 7 days at home or in public places. Other frequencies of secondhand smoke exposure (ie, ≥3 days, ≥5 days, and every day) during the past 7 days were also assessed. The weighted prevalence of secondhand smoke exposure was calculated according to the complex sample design for surveys. ResultsThe prevalence of secondhand smoke exposure in any place (home or public places ≥1 day during the past 7 days) decreased from 2013-2014 (72.9%, 95% CI 71.5%-74.3%) to 2019 (63.2%, 95% CI 62%-64.5%), as did exposure at home (2013-2014: 44.4%, 95% CI 43.1%-45.7%; 2019: 34.1%, 95% CI 33.1%-35.2%) and in public places (2013-2014: 68.3%, 95% CI 66.9%-69.6%; 2019: 57.3%, 95% CI 56%-58.6%). The prevalence of secondhand smoke exposure decreased with increased gross domestic product per capita in each of the 2 survey years irrespective of exposure frequency or location. The prevalence of exposure at other frequencies (ie, ≥3 days, ≥5 days, or every day during the past 7 days) also decreased in any place, at home, and in public places. Secondhand smoke exposure was associated with higher school grade level (ninth vs seventh grade: odds ratio [OR] 1.76, 95% CI 1.68-1.84), gender (boys vs girls: OR 1.18, 95% CI 1.15-1.22), urban status (urban vs rural: OR 1.10, 95% CI 1.01-1.19), and cigarette smoking (yes vs no: OR 6.67, 95% CI 5.83-7.62). ConclusionsAlthough the prevalence of secondhand smoke exposure among Chinese adolescents declined from 2013-2014 to 2019, it remains unacceptably high. More effective strategies and stronger action are needed in China to further, and dramatically, curb secondhand smoke exposure among adolescents.